Eco-consciousness in tourism: A psychological perspective on green marketing and consumer behavior - Yuxi Zhang; Hua Zhao; Umer Zaman (Acta Psychologica)
This research investigates the impact of eco-friendly marketing strategies on environmentally aware actions displayed by tourists in the Chinese hospitality sector. This research evaluates the relationships between green consumption value and pro-environmental self-identity and felt obligation to explain consumer behavior by applying the Stimulus-Organism-Response (S-O-R) model framework. A total of 437 hospitality consumers took part in the study, and data analysis was conducted using structural equation modeling. Result data indicates that eco-friendly marketing practices directly stimulate tourists to adopt sustainable behaviors. The relationships between these effects become stronger through the pathway influence of green consumption value and pro-environmental self-identity. Felt obligation strengthens the relationships between these variables because it increases the likelihood of people taking eco-conscious actions. The research demonstrates practical and theoretical value by showing businesses how to use green marketing effectively for sustainability promotion in hospitality operations. The study indicates that organizations must unite identity-based marketing with value-based methods to encourage environmentally sustainable actions that advance worldwide conservation programs.